Competition law, regulation, and digital platforms Japan, China, UK, EU and USA - Taplin, Ruth; Fuchikawa, Kazuhiko (Routledge studies in the growth economies of Asia, 2025)
"This book confronts and analyses how competition law in its present form is unable to deal with the new advances in digital technology that have made tech giants not subject to national jurisdictions as they straddle the world, with a particular focus on Japan, China, UK, EU and USA. Demonstrating how the gatekeeping role of digital platforms has broken through the boundaries of national regulation, this book highlights examples where companies have broken and infringed antitrust law with impunity, pursuing self-preferencing/ unfair competition practice for solely their own profitability. It also identifies how tech giants can open their digital platforms for fair use by consumers, SMEs and creators while still allowing tech giants to maintain their important role as gatekeepers of digital security that protects users from cyberattacks. This is followed by an examination of the similarities between tech giants and big pharma within the competition law and intellectual property context, revealing how tech giants are beginning to target the healthcare sector. Exploring how intellectual property rights are interwoven through new modernising regulations to curtail the dominance of Big Tech on digital platforms, this book will appeal to students, scholars and practitioners of Business Ethics, Intellectual Property, Law and Regulation"--